Senecavirus A - Uma abordagem biotecnológica para a vigilância em doenças vesiculares - Juliana da Silva Gomes (2022)
RIEGER, Juliana. S.G., Universidade Federal do Mato Grosso do Sul, Dezembro, 2022. Senecavirus A – Uma abordagem biotecnológica para a vigilância em doenças vesiculares. Orientador: Dr. Edgar Julian Paredes Gamero. Co-Orientadora: Dra Lenita Ramires dos Santos. Senecavirus A (SVA) is a nonenveloped, single-stranded RNA virus of the genus Senecavirus, family Picornaviridae. This virus causes a vesicular disease in swine, clinically indistinguishable from other vesicular diseases, such as foot-and-mouth disease (FMVD), swine vesicular disease (SVD), vesicular stomatitis (VS) and vesicular exanthema of swine (VES). The clinical signs are vesicular lesions in sows and acute death in piglets. In Brazil, outbreaks were reported initially in the end of 2014, and since then, it has been disadvantageous on swine production, most the economic importance of the disease is related to similarity with FMVD. In this study, recombinant Viral Protein 2 (VP2) protein was produced to develop an indirect ELISA assay to identify the presence and levels of antibodies against SVA in Brazilian swine herds. Sensitivity and specificity values of the VP2 ELISA were determined using ROC analysis performed with 43 positives samples and 219 negatives samples. In addition, serum samples from swine immunized with eight distinct Brazilian SVA inactivated strains (MF615501, MF615502, MF615503, MF615505, MF615506, MF615507, MF615509 and MZ456812) were tested in the VP2 ELISA. Cross-reactivity with VS was tested with sera from 17 pigs naturally-infected with sera from positive animals for this disease. The results about SVA VP2 indirect ELISA, assuming a 100% specificity, the test showed 74.4% sensitivity. In the onset of clinical signs, sensitivity was 100% and 9 months after the onset, sensitivity was 73.35%. The VP2 ELISA was able to detect specific antibodies in sera from swine that received three of the eight Brazilian SVA inactivated strains. The VP2 ELISA developed here was able to detect specific antibodies of SVA in acute and recovered pigs and no cross-reaction with SV. This assay is a useful tool in monitoring the disease and could help to improve the disease diagnosis.